Sociology of Designs: Pot Designs Favored by Residents of Middle-Class Housing Cluster for Gardening Activities During the Pandemic - Ariani, Ariani; Rizali, Awang Eka Novia; Armas, Anita; Ferbian, Kelvin (Komunitas, 2022)
Currently, gardening is one of the popular activities during the COVID-19 pandemic situation to relieve boredom and psychological pressure. The phenomenon that occurs in people's behavior in responding to this trend, especially residents of middle-class housing clusters, is an interesting research subject. Specifically, this qualitative research with a design sociology approach aims to determine the criteria for pot design that people are interested in, as well as to provide recommendations for suitable pot designs for home gardening activities. Residents of the middle-class housing cluster were chosen as the target for obtaining data, based on the limitation of yard that leads to pots usage for planting. The data was collected from 104 respondents through questionnaires, interviews, and field observations. Based on the results of data analysis, the following pot design criteria were obtained: using clay material, minimalist shape, easy to move, come in different sizes, natural color, easy to obtain, and affordable in price. The results of the study in the form of design recommendations were then implemented with reference to these criteria, involving pottery craftsmen from the pottery center of Pundong, Bantul Regency, Special Region of Yogyakarta.